Network Security Centers as the GosSOPKA Forses - Mesengiser, Yakob Y.; Malakhov, Mark A.; Miloslavskaya, Natalia G. (Bezopasnostʹ informat͡s︡ionnykh tekhnologiĭ, 2022)
The paper addresses the need to create a Network Security Center (NSC), and the functions of the NSC and infrastructure requirements on the basis of security requirements imposed by the subjects of the critical information infrastructure (CII) of the Russian Federation (RF) to ensure the safety of CII objects of the RF. The current work describes the NSC as the forces of the State System for Detecting, Preventing and Eliminating the Consequences of Computer Attacks Aimed at the Information Resources of the RF (GosSOPKA). As part of the work, the following tasks are solved: a list of regulatory bodies regulating the processes and security measures presented to the subjects of the CII of the RF to ensure security of objects of the CII of the Russian Federation as well as these processes and measures themselves are determined; Security Operations Centers (SOCs) and NSCs as the GosSOPKA forces are described. It is possible to use the results obtained in the framework of the processes of organizing cooperation with GosSOPKA, and the creation of a NSC dealing with computer attacks, detecting and responding to incidents around the clock; and a training course dedicated to the CII security.